Pengembangan Buku Scientific Approach Berbasis QR Code Berintegrasi Kahoot - Hanit Nikmahtul Kusumaningtyas; Luqman Hakim (Jurnal Pendidikan Ekonomi)
The development research produced a scientific approach textbook on the subject of Sharia Financial Instution Services based on QR Code and integrated kahoot for student XI class in semester I of sharia banking expertise. The purpose of study is to determine the development process of textbook, the feasibility of textbook dnd students responses of textbook wich is using BSNP standard. The 4-D model (Define, Design, Develope, Disseminate) from Thiagarajan was used as a development model of textbook. The results of the feasibility of islamic financial instution service textbook show an average material, language and graphic worth of 86,72% with very valid criteria. The result of product trial showed a precentage of 95,6% with veriy valid criteria. Thus, Sharia Financial Instution Service textbook is declared to be very valid and can be used in the learning process.DOI: https://dx.doi.org/10.17977/UM014v13i22020p84